Morgan Thomson: capstone - Thomson, Morgan, artist (Colorado State University. Libraries, 2016)
The artist's statement: Over the years my art, like myself, has grown. We both became more mature and more focused. Some of my artworks show an inner chaos, brought to the form of fiber arts, as well as typography. However, as some of my more recent work shows, I found focus on simplicity and purity. I worked with unedited photographs that allowed me to experiment with a medium that I hadn't worked with before. I found inspiration in Rene Azcuy, a Cuban graphic design artist. He inspired me to simplify my designs into monochromatic color schemes with a very selective amount of another color thrown into the piece. My focus has morphed into one that seeks the challenge of simplicity in as many ways as possible and will be for the foreseeable future.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design